SCREENING HIGH RESOLUTION COMPUTED TOMOGRAPHY (HRCT) CHEST AMONG PATIENTS UNDERGOING CARDIAC INTERVENTIONS DURING COVID-19 PANDEMIC; RADIOLOGICAL FINDINGS AND CLINICAL ASSOCIATIONS - Waseem Raja (Army Medical College Rawalpindi, 2020)
Objective: To study the HRCT chest findings in patients undergoing cardiac interventions during COVID-19 era.